The trunk segmental motion complexity and balance performance in challenging seated perturbation among individuals with spinal cord injury - Mianjia Shan; Chenhao Li; Jiayi Sun; Haixia Xie; Yan Qi; Wenxin Niu; Ming Zhang (Journal of NeuroEngineering and Rehabilitation)
Abstract Background Motion complexity is necessary for adapting to external changes, but little is known about trunk motion complexity during seated perturbation in individuals with spinal cord injury (SCI). We aimed to investigate changes following SCI in trunk segmental motion complexity across different perturbation directions and how they affect postural control ability in individuals with SCI. Methods A total of 17 individuals with SCI and 18 healthy controls participated in challenging sagittal-seated perturbations with hand protection. Upper arm activation was measured using surface electromyography for trial consistency. Motion complexity parameters, quantified across three degrees of freedom, was assessed using relative angular acceleration from six trunk segments obtained through motion capturing system. Motion performance parameters were assessed using center of pressure (CoP) measurements from a force plate, including settling time, maximum CoP displacement (MD) variability, and steady-state error. Statistical analyses examined group and direction differences, while complexity-performance relationships were evaluated using multiple response least partial squares regression. Results Compared to healthy controls, individuals with SCI showed significantly lower motion complexity in the lumbar and upper thoracic segments (approximately10% − 20%), with identical settling time and higher MD variability. Backward perturbations, as opposed to forward perturbations, resulted in reduced complexity in the aforementioned segments and increased steady-state error. Lower lumbar rotation complexity negatively correlated with MD variability (β = -0.240) and steady-state error (β = -0.485) in individuals with SCI, while showing a minor positive correlation with settling time (β = 0.152) during backward perturbation. Conclusion Simplified motion control in individuals with SCI may arise from uncoordinated lumbar and overactive thoracic neuromuscular control, compromising stability despite maintaining speed. Increasing lumbar motion complexity could enhance postural stability and accuracy during backward perturbation, representing a potential target for developing seated balance rehabilitation strategies and promoting more adaptive trunk control.